KARAKTERISTIK SISTEM PENDIDIKAN SUFISTIK: (Studi Tentang Tujuan Pendidikan, Pendidik, dan Peserta Didik dalam Tasawuf) - Prana Izza, Yogi (Universitas Nahdlatul Ulama Sunan Giri, 2022)
The three main components in the contemporary education system are educational goals, educators, and students. Although these three components have almost similar characteristics in the sufistic education system, there are substantive differences. The goals of sufistic education are tazkiyat al-nafs (purify the soul), tahdzib al-akhlak (diciplining morals), and al-ma'rifah (knowing of God). These goals are achieved through a learning process that is guided directly by a teacher who is called a murshid or sheikh. A teacher is an ideal figure with a competence of spiritual experience and clear transmit knowledge (sanad). The teacher also has a central role in the Sufistic education system. A teacher will guide a student (salik) with a pattern of interaction that seems undemocratic and leads to the cult of the individual teacher. However, it is done as a form of ethical interaction between a student and a teacher. The student has to carry out some strict ethical rules and heavy obligations from the teacher in order to shape the character of students and so that students reach their goals. Basically, a teacher knows the capacity of his students.